Validation and reference values of the EORTC QLQ-CML24 questionnaire to assess health-related quality of life in patients with chronic myeloid leukemia. Issue 3 (23rd February 2021) - Efficace, Fabio; Iurlo, Alessandra; Patriarca, Andrea; Stagno, Fabio; Bee, Ping-Chong; Ector, Geneviève; Capodanno, Isabella; Elena, Chiara; Bonifacio, Massimiliano; Blijlevens, Nicole M. A.; Caocci, Giovanni; Wan, Chonghua; et al.
Abstract: Health-related quality of life (HRQOL) assessment is important to facilitate decisions in the current treatment landscape of chronic myeloid leukemia (CML). Therefore, the availability of a validated HRQOL questionnaire, specifically developed for CML patients treated with tyrosine kinase inhibitors (TKIs), may enhance quality of research in this area. We performed an international study including 782 CML patients to assess the validity of the EORTC QLQ-CML 24 questionnaire, and to generate HRQOL reference values to facilitate interpretation of results in future studies. Internal consistency, assessed with Cronbach's alpha coefficients, ranged from 0.66 to 0.83. In the confirmatory factor analysis, all standardized factor loadings exceeded the threshold of 0.40 (range 0.49–0.97), confirming the hypothesized scale structure. Reference values stratified by age and sex were also generated. Our findings support the use of the EORTC QLQ-CML 24, in conjunction with the EORTC QLQ-C30, as a valuable measure to assess HRQOL in CML patients.